Contribution of small scale detonations to daily occupational noise exposure - Atencio, Victoria, author; Brazile, William, advisor; Sandfort, Delvin, committee member; Lipsey, Tiffany, committee member (Colorado State University. Libraries, 2013)
Hazardous levels of occupational noise exposure are of great concern due to the progressive nature of hearing loss. A one-time exposure to hazardous levels of noise may result in irreversible hair cell damage that could result in permanent hearing loss. This study focused on the contribution of small scale detonations to daily noise at Sandia National Laboratories (SNL). Personal noise monitoring was conducted for eleven employees to evaluate noise exposure for an eight hour period to determine the effects of small detonations and potential risk of noise induced hearing loss. Weights of various explosive materials ranged from 18 milligrams (mg) to 275 grams (g). Sound level meters were also used to determine if peak impulse noise measurements were under the occupational exposure limit of 140 dBC. Noise evaluations were conducted in five facilities that included two indoor boom boxes, two indoor firing pads, and one outdoor firing pad. The results of this study were used to conclude that no employees exceeded published exposure limits (85dBA, 3 dB exchange rate or 90 dBA, 5 dB exchange rate) nor at any point were employees exposed to noise levels above 140 dBC during detonations. According to SNL policy employers are required to enroll employees in a HCP if the 8-hr time weighted average (TWA) is greater than 85 dBA (3 dB exchange rate). A linear regression analysis was performed for each detonation location to determine the potential relationship between explosive weight and TWA for dosimetry results and peak levels of noise for sound level meter results. It was suggested that the relationship between explosive weight and LCPeak levels of the firing pad (p=0.283) and outdoor firing pad (p=0.801) were not statistically significant. Further, boom box activities had a significant relationship (p=0.001) however due to small sample sizes and variation of weights it is unclear whether the difference is due to explosive weight or activity. The p-values for ACGIH criteria (p=0.092) and OSHA criteria (p=0.34) were calculated and it was found that the linear relationship between explosive weight and TWA were not statistically significant. Based on the results of this field study and small sample sizes it was not possible to determine the explosive quantity at which hearing protection should be required. To determine the contribution of small scale detonations to daily noise exposures, noise samples that were collected during detonations were removed from employee TWAs. New TWAs were calculated and compared to the original data output. It was found that detonations increased employee ACGIH TWAs from only 1-8 dB. Impulse noise measurements obtained in this study were used to conclude that controls currently in place, including barriers, distance, and hearing protection, were effective means to employee safety and health.
Keywords: industrial hygiene; small scale detonations; noise exposure